Wet-chemically etched silicon nanowire: Effect of etching parameters on the morphology and optical characterizations. (February 2018) - Salhi, B.; Hossain, M.K.; Al-Sulaiman, F.
Graphical abstract: Highlights: This article aims to develop and characterize silicon nanowires and their applications. We are to investigate the metal-catalyzed electroless etching (MCEE) process on silicon. The influence of the fabrication parameters (hydrofluoric acid concentration, deposition time, and etching time) on the structure morphology, absorption, anti-reflection hydrophobicity properties were studied. Abstract: A two-step metal-catalyzed electroless etching (MCEE) of silicon wafer in HF/AgNO3 and HF/H2 O2 subsequently has been reported. Since the mechanism of nanowires (SiNWs) growth in MCEE route depends highly on etching process, we investigated the role of HF concentration and the etching time. The morphology and the optical absorption of the as-fabricated Si-based micro/nanostructured nanowires has been thoroughly investigated. It has been observed that the optical absorption characteristics were influenced by the etching time as well. An improvement by 10 of the absorption was obtained by increasing the etching time. Through finite-difference time-domain simulations it was observed that absorption, energy distribution, electric profile and generation get enhanced in presence of silicon SiNWs grown on bulk silicon. The experimental results reveal that the SiNWs produced by MCEE are very promising due to their potential application in photovoltaic devices.